Fluorescence Approach to Micellar Solubilization of an Aromatic Compound: P-Benzoquinone (p-BQ) - Mathur, Neha; Acharya, Seema (Asian Journal of Pharmaceutical Research and Development, 2018)
1,4-BQ or p-BQ are ubiquitous in nature and can be synthesized by diverse strategies. Quinones are the large class of compounds endowed with rich and fascinating chemistry. A large number of chemical derivatives with p-BQ as the basic subunit exhibit prominent pharmacological applications such as antibiotic, antimalarial, antitumor, antineoplastic, anticoagulant and herbicidal activity. Micellar solubilization of p-BQ in non-ionic and ionic surfactants monitored by fluorescence and absorption spectral techniques has been reported. The relatively week fluorescence of p-BQ was significantly enhanced in non-ionic micellar media formed by TX-100 surfactant. The influence of the surfactant, concentration and working experimental conditions on the fluorescence spectra of p-BQ is thoroughly evaluated and discussed. The solubilizing, action of the surfactants has been confirmed by the theoretically calculated spectral parameters like, empirical fluorescence coefficient, quantum yield, molar extinction coefficient and Stokes’ shift. The author provides a unique format for the analytical and medicinal applications of p-BQ based on micellization of the surfactants which makes them promising drug carriers, employing fluorescence, absorption and light scattering measurements. Keywords: Micelles, p-BQ, Fluorescence, Solubilization